Market Concentration and Risk-Taking in Banking Sector Listed on Indonesian Stock Exchange - Lailiyah, Elliv Hidayatul; Purwanti, Ika; Suyanto, Umar Yeni (Universitas Prasetiya Mulya, 2020)
The financial institution roles as the bank credit distribution. According to the banking surveys in Indonesia, it indicates that new credit growth has been strengthened. The increasing of credit leds to increase the level of risk taking by banks that its concentration of banking in a country plays in influencing banking risk taking. This study examined the effect of banking market concentration on bank risk taking. It also explored the moderating variable of bank size on the effect of market concentration on risk taking in the banking sector. The results of the study showed that the banking market concentration has the positive effect on banking risk taking. The size of the bank weakens the positive effect of market concentration on bank risk taking. The larger the size of the bank in a concentrated banking market, the lower the risk taking of the bank. The concentrated banking market requires to distribute the market share in banks to be carried out by banking regulators so that the banking market is not concentrated and reduces banking risk taking.Keywords:Â Market concentration, Risk-Taking, Bank Size* Department of Management, Institut Teknologi dan Bisnis Ahmad Dahlan Lamongan, Jalan KH. Ahmad Dahlan No.41, Lamongan, Jawa Timur, 62115Â https://doi.org/10.21632/irjbs.13.3.285-292